Interrelationship of PTSD, perceived health, and treatment satisfaction. Issue 1 (8th April 2014) - Astone-Twerell, Janetta; Morgen, Keith; Hsiao, Chu
Abstract : Purpose: – The residential therapeutic community (TC) treatment modality has been shown to effectively reduce drug use and improve psychiatric/medical health among clients who are often disproportionately impacted by medical conditions and have a co-occurring psychiatric disorder such as Posttraumatic Stress Disorder (PTSD). Yet not much is known regarding how clients' health may impact their treatment satisfaction. Using path analysis, the interrelationship between PTSD, perceived health, and treatment satisfaction was examined. The paper aims to discuss these issues. Design/methodology/approach: – A survey including the Posttraumatic Stress Disorder Checklist-Specific (PCL-S), a perceived health rating, and a Treatment Satisfaction Scale was collected from 303 clients at three comparable long-term residential TC treatment programs in New York City. Findings: – Findings indicated that clients with PTSD rated their health significantly worse than those without PTSD. Although no direct relationship between PTSD and treatment satisfaction was found, there was a significant positive correlation between perceived health and treatment satisfaction. Research limitations/implications: – Findings likely constitute a regional sample thus generalizability is limited. Practical implications: – Simultaneously addressing addiction, PTSD, and medical issues can improve clients' treatment satisfaction, consequently increasing treatment retention and producing greater positive post-treatment outcomes. Originality/value: – Few if any studies have examined the extent to which PTSD and perceived health impact treatment satisfaction within residential substance abuse treatment programs.